HUBUNGAN LETAK LESI HEMISFER SEREBRAL DAN DERAJAT KLINIS KECEMASAN PADA PENDERITA STROKE ISKEMIK - Yelly Marliana Patu,* Audry Devisanty Wuysang,* Nadra Maricar* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION STROKE IS THE LEADING CAUSE OF DISABILITY AND THE THIRD CAUSE OF DEATH IN THE WORLD THE LESION IN THE RIGHT HEMISPHERE IS MOST OFTEN ASSOCIATED WITH ANXIETY